Câmara Cascudo e seus "animais escritos" no Canto de Muro - Santos, Maria das Graças de Aquino (2018)
The work of thesis is based upon novel “Canto de Muro” (2006), by Câmara Cascudo (1898 - 1986 – Natal, Rio Grande do Norte). A qualitative, bibliographical and interpretative research, shows that the author acts as researcher, even when writing literary narratives considering that the piece in question was produced through daily observation of animal characters´ behavior. In this are considered small by society, as the cockroach, the bat, the mouse, the scorpion, among others, in their narrative acquire new values. They are redefined. In order to understand the thematic aspects present in this cascudian work, we sought support in the reflections of Merleau-Ponty (2002), Didi-Huberman (2010) and Nancy Huston (2010), regarding, respectively, poeticity in world observation, absence of an evident truth and the construction of truths through fiction. We articulate these reflections with the thought of the French Deleuze and Guattari (1995, 1996, 1997, 2002), with regard to nomadism, writing as a war machine, deterritorialization, minor literature, animal becoming and animal-writing. From this animal perspective, we also resort to Derrida's (2011) theory of the autobiographical animal. To dialogue with the ideas of this author, we establish relationships with the thoughts of Nascimento (2012) and Maciel (2016) on animality. In agreement with the proposed reflections, we have the theoretical support of Foucault (2013), Rancière (2009), Barthes (2003, 2004), Sousa (2006) and Loth (2014), showing that Cascudo poses as a thinker who, through literary writing, contributes to a different view of animals, thus evading the anthropocentric aspect. The issues developed by Cascudo, with respect to animals, are transverse routes, from the outside, in the folds, as directed by Levy (2011).